Organic matter decomposition patterns in the southern Adriatic and Ionian seas: observations from the ADREX cruise (PERSEUS project) - Caruso, Gabriella; Giani, Michele; Relitti, Federica; Kralj, Martina; La Ferla, Rosabruna; Franzo, Annalisa; Civitarese, Giuseppe (Biologia Marina Mediterranea, 2025)
The processes of organic matter decomposition via microbial enzymatic hydrolysis were studied in the southern Adriatic and Ionian Seas, areas characterized by ocean gyres and deep water formation, during the ADREX cruise (February 2014), to gain insights into the biogeochemical role of the microbial community. Proteolytic activity was predominant, followed by active decomposition of organic phosphates and polysaccharides. Dissolved enzymes contributed to organic matter recycling, especially at depth, suggesting the bioavailability of the pool of organic substrates. Correlations found between enzyme activity patterns and trophic variables suggested that microbial metabolism was driven by the organic substrates transported by water masses.